AB0534 When atherosclerosis is established, cardiovascular biomarkers are comparable in patients with ankylosing spondylitis, rheumatoid arthritis and psoriatic arthritis. (23rd January 2014) - Ikdahl, E.; Rollefstad, S.; Hisdal, J.; Provan, S. A.; Berg, I. J.; Stranden, E.; Kvien, T. K.; Olsen, I. C.; Semb, A. G.
Abstract : Background: Inflammatory joint diseases (IJD), including ankylosing spondylitis (AS), rheumatoid arthritis (RA) and psoriatic arthritis (PsA), are associated with an increased risk of cardiovascular (CV) disease and accelerated atherosclerosis. Objectives: Our goals were to evaluate CV risk factors in addition to soluble and vascular biomarkers in patients with IJD and established atherosclerosis, and to compare these parameters across AS, RA and PsA. Methods: Ninety-nine IJD patients, including 28 with AS, 58 with RA and 13 with PsA, were all diagnosed with carotid plaques, which is equivalent to established atherosclerotic disease. The patients were examined with the sphygmocor applanation tonometer to determine augmentation index (AIx), central systolic pressure and pulse wave velocity (PWV), three widely used parameters for arterial stiffness. Flow-mediated dilation (FMD) was used to assess endothelial function. The various biomarkers (adjusted for age and gender) were compared across AS, RA and PsA using ANCOVA. Results: Apart from differences in gender and medication, that could be attributable to the different natures of the diseases, demographic data showed that AS, RA and PsA patients were well matched. When comparing adjusted CV risk markers across AS, RA and PsA, the patient groups had comparable lipid profiles, CRP, ESR, systolic and diastolic blood pressures, PWV, central systolic pressure, intima media thickness (IMT) and FMD. However, the AS group had significantly lower AIx (p=0.004) (Table ). Image/graph: Conclusions: When atherosclerosis is established in patients with AS, RA or PsA, traditional CV risk factors, soluble and vascular biomarkers were comparable across the various IJDs. These findings may have clinical implications during cardiovascular risk evaluation in patients with IJD and needs further evaluation. Disclosure of Interest: None Declared